Priority setting in health care: Lessons from the experiences of eight countries - Lie Reidar K; Sabik Lindsay M (BMC, 2008)
Abstract All health care systems face problems of justice and efficiency related to setting priorities for allocating a limited pool of resources to a population. Because many of the central issues are the same in all systems, the United States and other countries can learn from the successes and failures of countries that have explicitly addressed the question of health care priorities. We review explicit priority setting efforts in Norway, Sweden, Israel, the Netherlands, Denmark, New Zealand, the United Kingdom and the state of Oregon in the US. The approaches used can be divided into those centered on outlining principles versus those that define practices. In order to establish the main lessons from their experiences we consider (1) the process each country used, (2) criteria to judge the success of these efforts, (3) which approaches seem to have met these criteria, and (4) using their successes and failures as a guide, how to proceed in setting priorities. We demonstrate that there is little evidence that establishment of a values framework for priority setting has had any effect on health policy, nor is there evidence that priority setting exercises have led to the envisaged ideal of an open and participatory public involvement in decision making.